PENCEGAHAN STUNTING MELALUI PROGRAM PMT INOVATIF BERBASIS OLAHAN DAUN KELOR DI DESA GUMELAR - Saputri, Alisah Marselia; Rizal, Mohammad Saiful; Sayuti, Muhammad Indra; Vidiansyah, Mohammad Rifki; Luthfiyah, Lenny (Department of Agronomy, Faculty of Agriculture, University of Jember, 2025)
This community service program was implemented in Gumelar Village, Balung District, Jember Regency, to increase community knowledge of stunting prevention through the innovation of PMT (Supplementary Feeding) based on local food processing from Moringa leaves. The program was implemented by 100 students participating in a collaborative community service program (Kuliah Kerja Nyata – KKN). The program implementation method used the Participatory Rural Appraisal (PRA) approach across three stages: planning, implementation, and evaluation. Activities included community outreach of stunting prevention with balanced nutrition, interactive discussions, and demonstrations on how to make the innovative product